2021
DOI: 10.1155/2021/6359652
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Alleviates Rheumatoid Arthritis in Rats through Inhibiting MTA1/HDAC1-Mediated Nur77 Deacetylation

Abstract: Ellagic acid (EA) was reported to play protective roles in rheumatoid arthritis (RA). It was found that the level of metastasis-associated gene 1 (MTA1)/histone deacetylase 1 (HDAC1) protein complex was downregulated by polyphenols in several human disorders. Notably, inhibition of MTA1 or HDAC1 has anti-inflammatory effects on RA. Therefore, our study is aimed at investigating whether EA prevents RA progression through regulating the MTA1/HDAC1 complex. Herein, the human fibroblast-like synoviocyte (FLS) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Moreover, an improvement in oxidative markers was observed, such as MPO activity, NO release, GSH levels, and lipid peroxidation. Similar doses of EA were used by Song et al (25, 50, 100 mg/kg/d), who confirmed the reduction of paw swelling, synovial hyperplasia, and inflammation in a collagen-induced arthritis (CIA) model [ 35 ]. Moreover, EA was treated in TNF-α-induced FLS cells, at the range of 10 to 100 μM, thus inhibiting the levels of cytokines (IL-6, IL-1β) and oxidative markers (MDA).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Moreover, an improvement in oxidative markers was observed, such as MPO activity, NO release, GSH levels, and lipid peroxidation. Similar doses of EA were used by Song et al (25, 50, 100 mg/kg/d), who confirmed the reduction of paw swelling, synovial hyperplasia, and inflammation in a collagen-induced arthritis (CIA) model [ 35 ]. Moreover, EA was treated in TNF-α-induced FLS cells, at the range of 10 to 100 μM, thus inhibiting the levels of cytokines (IL-6, IL-1β) and oxidative markers (MDA).…”
Section: Resultsmentioning
confidence: 66%
“…Plausibly, products from hydrolysis and metabolism, such as GA, EA, and UroA, participate in the biological effect, although their formation at the gut level has rarely been addressed. This evidence is supported by several in vivo experiments, in which HTs and metabolites were administered as individual compounds through the oral route at comparable doses: EA (50 mg/kg) ameliorated the inflammatory profile in RA models [ 31 , 32 , 33 , 34 , 35 ]; similarly EA, GA, and UroA (10–20 mg/kg) inhibited gut inflammation in IBD models [ 64 , 65 , 66 , 70 , 71 , 72 ], while EA (10 mg/kg) and GA (20–80 mg/kg) reduced allergic inflammation in AD, asthma, and rhinitis [ 86 , 88 , 96 , 102 ]. Remarkably, HTs have frequently been mentioned for direct antibacterial and antiviral activity [ 106 ], which may suggest a restrained impact on infection risk.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…There are relevant studies on the relationship between HDAC1 and inflammation. For example, down-regulation of HDAC1 can restore myocardial injury in septic mice to a certain extent ( Nong, Qin et al, 2022 ), and ellagic acid can alleviate rheumatoid arthritis in rats by inhibiting HDAC1 ( Song, Wu et al, 2021 ), and HDAC1 can control the metabolism of intestinal epithelial cells by regulating the supply of acetyl groups, resulting in impaired response to oxidative stress, AMPK kinase activation and mitochondrial biogenesis ( Gonneaud, Turgeon et al, 2015 ). Our study found that the expression of HDAC1 was significantly increased in the aorta of T2DM mice as well as HG-induced HUVEC cells ( Figures 3D, E, H , Figures 5A–C ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressed HDAC1 promotes the pathological process of bone destruction in RA. 17,18 Additionally, HDAC affects the differentiation of osteoclast progenitors by regulating NF-κB and RANKL/RANK signaling pathways. As potential antiinflammatory and immune drugs, HDAC inhibitors are promising in RA therapy.…”
mentioning
confidence: 99%